PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN SUMBER DAYA ALAM DALAM MENINGKATKAN POTENSI PEREKONOMIAN DAERAH PESISIR DI DESA KERTASARI - Nurmalasari, Baiq Linda; Wangi, Putri Azila; Triadi, M. Qiflan; Kartika, Raneta Mara; Putri, Ni Luh Eka Sudiawati; Chintami, Dinda Fasha; Sudana, I Wayan Pandu; Istifa, Lailatul; Insani, Raodatul; Juniardi, Nurdin (Universitas Mataram, 2025)
Kertasari Village is one of the villages in Labuhan Haji Subdistrict, East Lombok Regency, whose main economic base is in the agriculture and fisheries sectors. Despite its rich potential in dry land and agricultural/cash crop production, the village community faces serious challenges in the form of high poverty rates and health issues, particularly stunting and malnutrition among pregnant women. This situation is exacerbated by the suboptimal utilization and processing of agricultural products to meet families' nutritional needs sustainably. The University of Mataram's Community Service Program (KKN PMD) focuses on interventions based on the optimization of local resources. The aim is to reduce poverty rates, stunting, and early marriage by maximizing agricultural products for the nutritional needs of pregnant women, infants, and children. This is achieved through the optimization of agricultural/cash crop processing into value-added food sources by creating innovative products. The program aims to create smart farmers and a healthy generation by maximizing the potential of agricultural products, thereby realizing an independent and stunting-free Kertasari Village.